Environmental Attributes to Respiratory Diseases of Small Ruminants. (20th March 2014) - Rahal, Anu; Ahmad, Abul Hasan; Prakash, Atul; Mandil, Rajesh; Kumar, Aruna T.
Abstract : Respiratory diseases are the major disease crisis in small ruminants. A number of pathogenic microorganisms have been implicated in the development of respiratory disease but the importance of environmental factors in the initiation and progress of disease can never be overemphasized. They irritate the respiratory tree producing stress in the microenvironment causing a decline in the immune status of the small ruminants and thereby assisting bacterial, viral, and parasitic infections to break down the tissue defense barriers. Environmental pollutants cause acute or chronic reactions as they deposit on the alveolar surface which are characterized by inflammation or fibrosis and the formation of transitory or persistent tissue manifestation. Some of the effects of exposures may be immediate, whereas others may not be evident for many decades. Although the disease development can be portrayed as three sets of two-way communications (pathogen-environment, host-environment, and host-pathogen), the interactions are highly variable. Moreover, the environmental scenario is never static; new compounds are introduced daily making a precise evaluation of the disease burden almost impossible. The present review presents a detailed overview of these interactions and the ultimate effect on the respiratory health of sheep and goat.